The Relationship of Self-Confidence and Motivation with The Results of 25 Meters Breast Style Swimming - Al-Ma’arif Marantika, Surya; Wicaksono, Lungit; Siswoyo, Joan; Surisman (Universitas PGRI Palembang, 2024)
This study aims to determine: 1) the relationship between self-confidence and breaststroke swimming results in Siger Sembilan Swimming Club athletes; 2) the relationship between motivation and breaststroke swimming results in Siger Sembilan Swimming Club athletes; and 3) the relationship between self- confidence and motivation and breaststroke swimming results for Siger Sembilan Swimming Club athletes.This research is a quantitative descriptive study with a correlational approach. The research population consisted of swimming athletes at the Siger Sembilan Swimming Club, totaling 20 athletes. The sampling technique uses total sampling. The instrument for self-confidence and motivation uses a questionnaire, and breaststroke swimming achievement uses psychomotor tests. Data analysis uses product-moment correlation.The results of the research show that: 1) There is a significant relationship between self-confidence and the results of the 25-meter breaststroke swimming in Club Siger Sembilan athletes, with a value of rcount 0.776> rtable 0.444, 2) There is a significant relationship between motivation and the results of the 25-meter breaststroke swim in Club Siger Sembilan athletes, with a value of rcount 0.589> rtable 0.444. 3) There is a significant relationship between self-confidence and motivation and the results of swimming the 25-meter stroke in Club Siger Sembilan athletes, with a value of Fcount 13.077> Ftable (0.05) (1:17) 3,592. Keywords: breaststroke, motivation, self-confidence